Development Of a Mixture of Hydrogen and Nitrogen for The Synthesis of Ammonia and This Process. (Texas Journal of Multidisciplinary Studies, 2021)
The synthesis of ammonia requires a mixture of nitrogen and hydrogen in a ratio of 1: 3, and they can be separated in several ways. Nitrogen is obtained in industry by separation from liquid air. There are several methods for obtaining hydrogen from water and hydrocarbons, including iron-vapor and water electrolysis.